The Institute of Judicial Constitutional Control in the Post-Soviet States - K. A. Polovchenko (Vestnik MGIMO-Universiteta, 2013)
The article presents a comparative analysis of the European and the American model of judicial constitutional control. Exploring the reasons for the implementation of the European model of the constitutional control in the post-Soviet States of Eastern Europe and the CIS, the author comes to the conclusion that the introduction of the institution of the constitutional justice of the European design was a logical step in the establishment of constitutionalism in the region. Experience of the Western European States was taken into consideration while building the system of constitutional justice in the post-Soviet States of Eastern Europe and the CIS. However, we are not talking about blind copying of Western European experience, but rather of its creative processing taking into account the specifics of a particular State and its legal system.